The adoption of Japanese recruitment practices in Malaysia - Hooi, Lai Wan (Emerald Group Publishing Ltd., 2008)
Purpose - The objective of this research is to examine to what extent Japanese recruitment practices are introduced and practiced in the auto manufacturing companies in Malaysia, since the implementation of the Look East Policy. Design/methodology/approach - The process involves the gathering of both primary and secondary data, but the main method is a primary data survey. The approach is to target local enterprises as much as possible in the collection of primary data through a set of questionnaires, as well as in-depth interviews with the human resource (HR) directors and some employees of each company. Findings - It appears that the Malaysian manufacturing companies have not designed their recruitment practices after those of the Japanese. There is no one single model of recruitment practices operating in Malaysia, either among Japanese joint ventures or local enterprises. However, the findings do suggest the existence of some consistent sets of recruitment behavior among the companies, though it cannot be said with much confidence that these patterns are indeed representative of Malaysian recruitment behavior. Research limitations/implications - Research has been limited to the manufacturing industry only. Practical implications - HR practitioners can use the outcome of the study to gauge the adaptability of certain elements of Japanese recruitment practices to the Malaysian workplace. Originality/value - This paper offers an insight into the applicability of Japanese recruitment practices and offers practical help to HR practitioners embarking on new recruitment policies.